Konsep Spiritualisme Masyarakat di Era Modernisasi dalam Kehidupan Sosial-Beragama - Sandy Aji Suhada; Risladiba Risladiba; Iksan Sa’dudin; Engkus Kusnandar; Aah Syafaah (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to discuss the concept of community spiritualism in the era of modernization in religious social life. This study uses a qualitative approach by applying descriptive methods. The results and discussion of this study indicate that urban society, which is often synonymous with modern society, still tends to be individualistic, rationalistic, materialistic, and formalistic. It is this problem that causes society to continue to focus on following the trend of modernity, even though along with the development of the times it must be adjusted to the quality of spirituality in spiritual training so that it can lead itself to the right path that is not bound by lust. This study concludes that the essential meaning of spirituality is not material but rather a metaphysical concept that focuses on deepening the psyche where this is relevant to be actualized in modern society.